2023
DOI: 10.1186/s13018-022-03497-4
|View full text |Cite
|
Sign up to set email alerts
|

A novel digital arthrometer to measure anterior tibial translation

Abstract: Background Measurement of knee laxity after anterior cruciate ligament (ACL) injury is crucial for appropriate treatment and rehabilitation decision-making. This study examined the potential of a new digital arthrometer (Ligs, Innomotion, Shanghai, China) to quantify anterior tibial translation (ATT) in patients with ACL injuries and in healthy subjects. Methods A total of 60 participants included 30 subjects with single-leg ACL injuries and 30 hea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The straightforward and adaptable operation minimizes measurement inaccuracies that the examiner may have caused. Previous studies have confirmed the excellent intra-and interrater reliability (intraclass correlation, >0.9) of the Ligs arthrometer (Chen et al, 2022;Wu et al, 2023). Second, for the patient, the operation is more flexible because the rocker at the end of the main unit controls the load application.…”
Section: Figurementioning
confidence: 81%
See 2 more Smart Citations
“…The straightforward and adaptable operation minimizes measurement inaccuracies that the examiner may have caused. Previous studies have confirmed the excellent intra-and interrater reliability (intraclass correlation, >0.9) of the Ligs arthrometer (Chen et al, 2022;Wu et al, 2023). Second, for the patient, the operation is more flexible because the rocker at the end of the main unit controls the load application.…”
Section: Figurementioning
confidence: 81%
“…Load and displacement were input into the Ligs storage unit by using digital sensor with a sampling rate of 30Hz. Displacement recording was initiated when the load exceeded 20 N to attenuate the impact of muscle tissue ( Wu et al, 2023 ). The load is accurate to 1 N, and the displacement is accurate to 0.1 mm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors found higher accuracy than KT 2000 (sensitivity: 86% vs 83%; specificity: 95.5% vs 88.5%), using a threshold of 3 mm as in the study. Wu et al [ 28 ], recently tested a new automatic knee arthrometer (Ligs Innomotion). At a load of 150 N (comparable to the MMT in the present study), the authors found the maximum AUC (0.857) and a sensitivity and specificity of 0.87 and 0.73, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…A physical therapist unaware of the study measured anterior knee laxity before the surgery using the Ligs digital arthrometer (Innomotion Inc) at 90 N, 120 N, and 150 N thrust loads. 27,52,56 During the measurement, simultaneous stress radiography was conducted by a trained radiology technician with the assistance of the arthrometer to obtain a true lateral view radiograph of the knee at 30°o f flexion. 9,24 Anterior tibial translation was measured on the true lateral view radiograph by the same senior musculoskeletal radiologist using the method described by z Beldame et al 4 The side-to-side difference (SSD) in knee laxity measured by the arthrometer and stress radiography at 90 N, 120 N, and 150 N was calculated, respectively.…”
Section: Patient Assessmentmentioning
confidence: 99%